Campaign Contributions and Congressional Voting: A Simultaneous Probit-Tobit Model - Chappell, Henry W. (The Review of Economics and Statistics, 1982)
Full-information maximum likelihood (FIML) estimates of the simultaneous probit-Tobit (SPT) model suggest that effects of campaign contributions on voting are smaller than single equation probit estimates would indicate. The author has generally unable to conclude that contributions have a significant impact on voting decisions, apparently votes are most often decided on the basis of personal ideology or preferences of constituents. These findings differ markedly from earlier results of economists Gary C. Durden and Jonathan J. Silberman, whose single equation models showed a substantial impact of contributions on voting decisions. Despite the lack of significance according to model SPT, it would not, however, be appropriate to unambiguously conclude that contributions have no effects on voting. For six of eight coefficients the anticipated positive sign resulted and one coefficient remained marginally significant. The article also shows that the lack of significance is attributable not only to smaller coefficient size, but also to larger standard errors. The FIML estimates of the contribution coefficients are not very precise.